2012
DOI: 10.1186/1471-2202-13-143
|View full text |Cite
|
Sign up to set email alerts
|

Functional crosstalk in culture between macrophages and trigeminal sensory neurons of a mouse genetic model of migraine

Abstract: BackgroundEnhanced activity of trigeminal ganglion neurons is thought to underlie neuronal sensitization facilitating the onset of chronic pain attacks, including migraine. Recurrent headache attacks might establish a chronic neuroinflammatory ganglion profile contributing to the hypersensitive phenotype. Since it is difficult to study this process in vivo, we investigated functional crosstalk between macrophages and sensory neurons in primary cultures from trigeminal sensory ganglia of wild-type (WT) or knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…As recently reviewed [28], [29], the cellular effects of TNFα are mediated by two distinct receptor classes (TNFR1 and TNFR2).While TNFR1 is ubiquitously expressed and is canonically considered to be a pro-apoptotic signal in cell death pathways, TNFR2 expression is restricted to immune cells like microglia and macrophages, neurons and oligodendrocytes. In view of previous reports that neuroinflammation might be contributory to sensitize neurons in migraine attacks [9], [18], [30], [31], we first investigated whether mouse trigeminal ganglion neurons could respond to TNFα as evidenced by their expression of the TNFα receptor TNFR2 ([32]; Fig. 1A, B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently reviewed [28], [29], the cellular effects of TNFα are mediated by two distinct receptor classes (TNFR1 and TNFR2).While TNFR1 is ubiquitously expressed and is canonically considered to be a pro-apoptotic signal in cell death pathways, TNFR2 expression is restricted to immune cells like microglia and macrophages, neurons and oligodendrocytes. In view of previous reports that neuroinflammation might be contributory to sensitize neurons in migraine attacks [9], [18], [30], [31], we first investigated whether mouse trigeminal ganglion neurons could respond to TNFα as evidenced by their expression of the TNFα receptor TNFR2 ([32]; Fig. 1A, B).…”
Section: Resultsmentioning
confidence: 99%
“…As P2X3 receptors in the brain and spinal cord are almost exclusively expressed on sensory neurons that transfer nociceptive signals to higher centers [7], [8], unraveling the primary mechanism may have significant relevance to understanding the generation of migraine-relevant pain processes. Since extracellular ATP levels are usually low [9], P2X3 receptors are not continuously activated under basal conditions in WT sensory neurons. However, constitutively up-regulated P2X3 receptors as seen in R192Q KI sensory neurons, are responsive already after application of low doses of the selective agonist α,β-methyleneadenosine 5-triphosphate (α,β-meATP) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our western blot analysis suggested that TRPM2 protein is expressed in neurons in TG. However, we acknowledge that our SGC-enriched TG cultures might also contain other cell types such as Schwan cells and macrophages (Glenn et al, 1993; Franceschini et al, 2012). Thus, our study suggests novel mechanisms involving TRPM2, a sensor of oxidative stress, by which peripheral inflammation leads to the production of cytokines and chemokines in both neurons and non-neuronal cells including SGCs that envelop neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammatory cells like macrophages releasing TNFα can further upregulate P2X3 receptor activity (Franceschini et al, 2012, 2013). It is also noteworthy that human P2X3 receptors recover about twice faster than analogous rodent receptors (Pratt et al, 2005).…”
Section: Functional Role Of Desensitization Of P2x3 Receptorsmentioning
confidence: 99%